Avis Spirituels Pour les ames Qui Aspirent a la Perfection (Ancienne Maison Charles Douniol, 1897)
Keywords: 1.Conservation 保護; 18.Bookworm

Boletim Official do Governo da Provincia de Macau (1897)
Keywords: 2.Damage

Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1897)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Francisco Suarez (Imprensa da Universidade, 1897)
Keywords: 1.Conservation 保護; 18.Bookworm

Manual dos Zeladores e Dos Associados (Administracao do Novo Mensageiro do Coracao de Jesus, 1897)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Mez do Sagrado Coracao de Jesus (Livraria Catholica, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Recte et Immobiliter, o com se habria hecho santo (Libreria y Tipografia Catolica, Pino, 1897)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Religiao, Moral e Politica (Manoel Gomes, Editor, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護.; 15.Stain 污漬; 2.Damage

Trechos selectos do padre antonio Vieira 1697-1897 (Typographia Minerva Central, 1897)
stamp of A.S.M
Keywords: 18.Bookworm; Good

Vita et Doctrina Jesu Christi e Quatuor Evangelistis - Avancinum, N. (Typis Societatis Missionum Ad Exteros, 1897)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Leituras allemãs - Beck, Th (Guillard, Aillaud, 1897)
OCLC: 320046987
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; languages

Os Episocios Miraculosos de Lourdes - D'aguilar, Francisco D'azeredo Teixeira (Livraria Chardron, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Beautiful Pearls of Catholic Truth Containing the Teaching of the Holy Catholic Church - Fitzgerald, Thomas M. (In the office of the Librarian Congress, 1897)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Oeuvres polémiques de Mgr Freppel .. - Freppel, Charles-Émile (P. Téqui, 1897)
Stamp
Keywords: 22.stamp; Condition: Fair; Religion

Oeuvres polémiques de Mgr Freppel .. - Freppel, Charles-Émile (P. Téqui, 1897)
Stamp
Keywords: 10; 22.stamp; Condition: Fair; Religion

Catecismo de Perseveranca - Gaume, J. (Livraria Chardron, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

La Steie Chretienne de Si-Ngan-Fou - Havret, P. Henri (Imprimerie De la Mission Catholique, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Scripturae Sacrae, Commentarius in Exodum et Leviticum - Hummelauer, Francisco de (Sumptibus P. Lethielleux, Editoris, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Recte et Immobiliter! O como se Habria Hecho Santo - Kreinten, P. W. (Libreria y Tipografia Catolica, Pino, 1897)
Stamp
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

新經譯義 - Laurent Li Wen-yü (土山灣印書館, 1897)
聖若瑟書院藏書印，尾頁：聖保祿行程圖
OCLC: 1554107683

Table Analytique des oeuvres oratoires de Bossuet - Lebarq, L'abbe J. (Societe de Saint- Augustin, 1897)
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Historia da litteratura segundo o programma official de 18 d'Outubro de 1889 para a cadeira de Litteratura Nacional dos lyceus - Maia, Delfim Maria de Oliveira (Livraria Portuense de Lopes & Cª, 1897)
Signature
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; History

Meditacoes sobre A Eucharistia - Mons. De La Bouilleirie (Imprensa Commerical, 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Oeures Completes de Saint Francois de Sales - Sales, S. Francisco de (Libraire de Louis Vives, Editeur., 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Oeures Completes de Saint Francois de Sales - Sales, S. Francisco de (Libraire de Louis Vives, Editeur., 1897)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

A Alma aos Pes de Jesus - Sinibaldi, Thiago (Typ. Franca Amado, 1897)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Estudos philosophicos - Vaz, Francisco Manuel (Typ. a vapor José da Silva Mendonça, 1897)
OCLC: 958984238
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy

Monita et Exempla - Xaverii, S. Francisci (Typis Collegii S. Joseph, 1897)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage